VD_FINDINFO HC / 2020 / 614 vom 22. Dezember 2020 - VD Tribunal cantonal (2020)
PRÉVOYANCE PROFESSIONNELLE, OBLIGATION D'ENTRETIEN, DIVORCE, MAJORITÉ{ÂGE}, MAXIME OFFICIELLE | 124b al. 1 CC, 124b al. 2 CC, 117 let. a CPC (CH), 296 al. 3 CPC (CH), 315 al. 1 CPC (CH), 317 CPC (CH)